Uso de estatina e eventos cardiovasculares em pacientes admitidos com síndrome coronariana aguda - Neto, Curt Vieira (2015)
Background: It has been proven the effectiveness of statin use, both in primary prevention, as in the secondary. However, there are few national studies confirming this protection in patients with acute coronary syndrome (ACS). Objectives: To evaluate the association between the previous use or nonuse of statins and in-hospital outcome in patients with ACS. Methods: It is observational, cross-sectional, retrospective, from 2004 to 2011 with 454 patients from the SOLAR record, divided into G1 (yes) and G2 (no), according to the previous use of statins. The groups were compared for the presentations of ACS and for the occurrence of death, acute myocardial infarction (AMI), cerebrovascular accident (CVA) and cardiopulmonary arrest (CPA). Results: The G1 consists of 157 subjects ( 34.5 % ) compared to G2 , with 297 subjects (65.5 % ) had unstable angina ( 45.9 % vs. 30.0 % ; p = 0.001) , while the G2 showed more AMI with ST segment elevation (24.2% vs 15.3% ; p = 0.026 ) . There was no difference between groups in the occurrence of myocardial infarction without ST elevation (7.6% vs 9.5%; p = 0.669). Members of the G1 had a lower rate of death (0,6% vs 4.1%; p = 0.040) and CRP (0 vs 3.0%; p = 0.031). For the presence of death, stroke and re- infarction, G1 and G2 had similar behavior ((7.6% vs 9.5%; p = 0.669) Conclusion: In patients with ACS, previous use of statins confer less severe clinical presentation and more favorable in-hospital outcome than those who did not use the drug.